Superconductivity as a Bose-Einstein condensation? - Adhikari, S. K.; Casas, M.; Puente, A.; Rigo, A.; Fortes, M.; Solis, M. A.; de Llano, M.; Valladares, A. A.; Rojo, O. (Elsevier B.V., 2000)
Bose-Einstein condensation (BEC) in two dimensions (2D) (e.g., to describe the quasi-2D cuprates) is suggested as the possible mechanism widely believed to underlie superconductivity in general. A crucial role is played by nonzero center-of-mass momentum Cooper pairs (CPs) usually neglected in BCS theory. Also vital is the unique linear dispersion relation appropriate to weakly-coupled bosonic CPs moving in the Fermi sea-rather than in vacuum where the dispersion would be quadratic but only for very strong coupling, and for which BEC is known to be impossible in 2D.